2016
DOI: 10.1177/0002716216678591
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Contraceptive Use and Health Facility Choice among Young Women in Malawi

Abstract: We explore whether differential access to family planning services and the quality of those services explain variability in uptake of contraception among young women in Malawi. We accomplish this by linking the Malawi Schooling and Adolescent Study, a longitudinal survey of young people, with the Malawi Service Provision Assessment collected in 2013–2014. We also identify factors that determine choice of facility among those who use contraception. We find that the presence and characteristics of nearby facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Several behavioral and environmental factors have been suggested to affect correct usage, continuity and method of contraceptives preferred by AGYW. For instance, the age at sexual debut, coerced sexual intercourse, age disparate sexual relationships was associated with influencing contraceptive use [12,13]. In spite of these factors, the South African government continues to be committed to improving usage of contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…Several behavioral and environmental factors have been suggested to affect correct usage, continuity and method of contraceptives preferred by AGYW. For instance, the age at sexual debut, coerced sexual intercourse, age disparate sexual relationships was associated with influencing contraceptive use [12,13]. In spite of these factors, the South African government continues to be committed to improving usage of contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…289 changes in contraceptive use and fertility. 25,36,37,38 Similarly, cultural norms about marriage likely 290 play a major role in the contraceptive decisions among these women , 25,29 After controlling for 291 these factors, we found that the adjusted odds of a woman using a modern contraceptive was 292 three times as high in areas with strong implementation compared to those with weaker 293 implementation.…”
Section: Resultsmentioning
confidence: 83%
“…22,23,24 Yet, very few of these studies include outreach services or analyze the combined 105 impact of the implementation of multiple FP programs at the national scale. 25,26,30 We conducted 106 an Implementation Strength Assessment (ISA) in 2017 to measure the strength of FP programs 107 delivered across the community and facility levels in Malawi and developed a summary measure 108 that reflects the combined implementation strength of FP programs across these levels. 27 Using 109 this summary measure, this paper reports on the association between the implementation strength 110 of FP programs and modern contraceptive use among Malawian women.…”
mentioning
confidence: 99%
See 2 more Smart Citations